Catalog of the horse-flies (Diptera: Tabanidae) of Chile - González, Christian R.; Elgueta, Mario; Krolow, Tiago K.; Henriques, Augusto L. (Zootaxa, 2022)
A catalog of the Tabanidae from Chile is provided. All valid names and synonyms for the 116 species and 25 genera known for the country including information about name, author, year of publication, page number, type species, type locality and references are listed. The species Dasybasis albohirta (Walker) is cited for the first time for Chile. The type locality of Dasybasis nigrifrons (Philippi) is corrected to Chile (Todos Los Santos Lake). The dates of the description of Tabanus nigrifrons Philippi (now Dasybasis), and Pangonia australis Philippi (now Pseudoscione) are corrected from their original description by Philippi; the original description dates for Tabanus andicola (now Dasybasis), and Tabanus magellanicus (now synonym junior of Dasybasis trita (Walker)) are corrected from 1865 to 1862. Three species previously recorded from Chile are deemed to have been misidentified or misrecorded from Chile: Esenbeckia (E.) cisandeana Wilkerson & Fairchild and Esenbeckia (E.) enderleini Kröber, and Esenbeckia (E.) testaceiventris (Macquart, 1848). The genus Dasybasis Macquart is the richest genus in Chile, with 33 species. Seven genera (Mycteromyia Philippi, Promycteromyia Coscarón & Philip, Archeomyotes Philip & Coscarón, Austromyans Philip & Coscarón, Chaetopalpus Philippi, Pseudomelpia Enderlein, and Sixtomyia Krolow, Henriques & González), three subgenera (Esenbeckia (Astomyia) Burger, E. (Palassomyia) Fairchild, and Protodasyapha (Protodasyapha) Enderlein), and 64 species are known only from Chile. There are also one subgenus (Protodasyapha (Curumyia) Coscarón), and 36 specie with distribution shared only between Chile and Argentina.